2021
DOI: 10.1016/j.jpedsurg.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic malformations adjacent to the airway in neonates: Risk factors for outcome

Abstract: To evaluate imaging, treatment, and outcomes in neonates with a lymphatic malformation (LM) adjacent to the airway and to evaluate risk factors that can predict outcome. Methods: A retrospective case series was conducted of ten patients treated between January 2011 and July 2019. The main outcome measures included airway compromise and clinical response to sclerotherapy ± surgery. Categorical data were compared using the Fisher's exact test. Results: Ex-utero intrapartum therapy was performed in four cases, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…After full-text screening against inclusion criteria, 168 articles, accounting for 6,761 procedures, were selected ( Figure 1 ) ( 11 – 178 ). Fourteen of the included studies, not providing information on the procedure outcome, were only considered for the initial description of anesthesia modality and in the summary of anesthetic drugs used ( 13 , 25 , 31 , 42 , 53 , 60 , 66 , 109 , 110 , 123 , 142 , 147 , 148 , 165 ). Characteristics of the included studies can be found in Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
“…After full-text screening against inclusion criteria, 168 articles, accounting for 6,761 procedures, were selected ( Figure 1 ) ( 11 – 178 ). Fourteen of the included studies, not providing information on the procedure outcome, were only considered for the initial description of anesthesia modality and in the summary of anesthetic drugs used ( 13 , 25 , 31 , 42 , 53 , 60 , 66 , 109 , 110 , 123 , 142 , 147 , 148 , 165 ). Characteristics of the included studies can be found in Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
“…Life-threatening complications such as airway compromise may require either an orotracheal intubation or a tracheostomy before treatment, including ex utero intrapartum treatment (EXIT) procedure when prenatal diagnosis is made [ 2 , 4 , 27 ]. Recent studies showed that sclerotherapy was a safe and effective procedure to rapidly reduce the size of the lesion [ 28 , 29 ]. Surgery can be also considered, as well as systemic treatment with Rapamycin (Sirolimus ® ) in spontaneously breathing neonates [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI gives important additional information regarding tissue differentiation, which aids in differentiating between benign and malignant tissue and between a venous and lymphatic malformation. In addition, MRI is very helpful in the assessment of the extent of the CVM and its relation with adjacent structures [29]. For AVMs, digital subtraction angiography (DSA) is the gold standard diagnostic method, owing to its capacity to confirm AV-shunting, assess the angioarchitecture of the nidus, As in VMs, the majority of LMs can be classified as common LMs within the ISSVA classification; however, sometimes LMs appear as complex lymphatic anomalies.…”
Section: Diagnosismentioning
confidence: 99%